A new approach to enhance the thermoelectric performance of quaternary chalcogenides copper zinc tin sulfide thin films by varying copper molar concentration. (1st February 2023) - Ashfaq, A.; Mufti, Hareem; Javaid, K.; Mahmood, K.; Ikram, Salma; Ali, A.; Amin, N.; Ali, M. Yasir; Ilyas, S.Z.; Aslam, Bilal; Ali Khan, Eng Arshad; Hussain, S.
Abstract: This manuscript revealed an enhancement in the thermoelectric performance of quaternary chalcogenides Cu2 ZnSnS4 (CZTS) TFs by the copper (Cu) atoms (1–2.5 mM) modulation during solution growth. Thermo-power data suggested that various performance parameters such as electrical conductivity (σ), Seebeck coefficient (S) and thermo-power factor (P) were improved significantly [(19–183 S/cm), (97–884 μV/ ° C) and (1.78 × 10 −5 –1.43 × 10 −2 Wm −1 K −2 )] when the atomic concentration of Copper atoms increased from 01 to 2.5 mM respectively. This trend of thermo-power for CZTS thin films is correlate with development of additional holes along with the generation of Cu based secondary phases. The presence of extra/secondary phases due to additional Cu atoms is supported by some supplementary measurements. XRD data confirmed that some Cu based extra phases were developed at higher concentration of Cu atoms. Raman spectroscopy measurements further revealed that the intensity of Cu based extra/secondary phases was noticed towards higher values when the molar ratio of Cu atoms increased. SEM micrographs demonstrated the rougher surface of CZTS samples which were prepared using higher concentration of Cu when compared with lower concentration samples. UV/VIS Spectroscopy data further confirmed our argument that numbers of other secondary phases were expended with the concentration of Cu atoms. Highlights: Growth of CZTS by sol-gel with varying concentration of Cu atoms. Thermoelectric properties enhanced by increasing Cu concentrations due to emergence of secondary phases. Presence of secondary phases verified by XRD, Raman Spectroscopy, SEM and UV.